Ensaio de cone de penetração dinâmica para avaliação do subleito de via férrea - Schlögel, Caio Vinícius (2020)
This work aims to assess the use of the Dynamic Cone Penetrometer (DCP) as a tool to evaluate in situ bulk dry density of the soil, thus helping engineers and staff in the quality control assurance of the soil. Besides that, another objective is to develop a practical and useful methodology to evaluate degree of compaction (DC) of a soil, aiding in the development of maintenance plan for railroad infrastructure. Nowadays, the most common in situ test to evaluate the soil bulk dry density is the sand replacement test, but it is known that such test demands some sort of excavation, extra resources as a scale to weight the material replaced, therefore making it time consuming. Based on that, this thesis objective is to study the DCP as an easy and functional tool to in situ tests. The area chosen to be studied is located nearby the city of Itu, state of São Paulo, Brazil. The study correlates in situ and laboratorial tests in order to obtain an association between de penetration of the DCP (DN) and bulk dry density (ρ). It is expected to obtain a satisfactory correlation between DN and ρ and develop an easy and practical methodology to estimate degree of compaction in situ. The results collected from the estimation of the compaction degree were considered satisfactory based on the valued of standard error and margin of error obtained from the correlation of bulk dry density, moisture content and DN, especially in smaller distances, circa 5 km. However, the methodology designed for aiding the development of maintenance plans showed flows especially if considers the effect of moisture content of the soil on the results.